(Un)receptiveness in interactions with professionals: experiences of parents of children with retinopathy of prematurity - Beatriz Castanheira Facio; Bruna de Souza Lima Marski; Ieda Harumi Higarashi; Maira Deguer Misko; Aline Oliveira Silveira; Monika Wernet
Abstract OBJECTIVE To analyze the influence of health professionals' receptiveness on parental care of children with retinopathy of prematurity (ROP). METHOD A qualitative study developed under the theoretical framework of Symbolic Interactionism and using a narrative research methodology. Six women and three men, being parents of children with retinopathy of prematurity were individually interviewed in depth. RESULTS From the scope of information, emotions and their rights, the parents experienced receptiveness from some professionals and unreceptiveness from others. The predominance of unreceptive attitudes in the parental narratives originated the following analysis themes: Informational (un)receptiveness, Emotional (un)receptiveness, and (Un)receptiveness of rights. CONCLUSION The study supports human and comprehensive healthcare in the context of retinopathy of prematurity by pointing out the interactive process with health professionals as a potential stressor of parental care. The results signal a nuclear of attitudinal changes and reinforce challenges to the child and family-centered approach.